Skeletal muscle gene expression and meat quality of F1 Angus–Nellore young steers and bulls feedlot finished - Santiago, Bismarck M. [UNESP]; Baldassini, Welder A. [UNESP]; Chiaratti, Marcos R.; Pandey, Anand K.; Torrecilhas, Juliana A. [UNESP]; Torres, Rodrigo N.S. [UNESP]; Ribeiro, Richard V. [UNESP]; Lanna, Dante P.D.; Pereira, Guilherme L. [UNESP]; Curi, Rogério A. [UNESP]; Chardulo, Luis Artur L. [UNESP]; Machado Neto, Otávio R. [UNESP] (Elsevier, 2023)
This study investigated the effects of castration on skeletal muscle gene expression and beef quality. Six-hundred and forty F1 Angus–Nellore steers and bulls (initial body weight of 299 and 297 ± 4.1 kg, respectively) feedlot finished were used. Gene expression revealed that steers showed up-regulation (P<0.05) of acetyl-CoA carboxylase alpha, fatty acid-binding protein, fatty acid synthase, peroxisome proliferator activated receptor (PPAR)-gamma and stearoyl-coa desaturase, while bulls shown higher expression of PPAR-alpha and sterol regulatory element-binding protein 1. Consequently, steers had greater (P<0.01) intramuscular fat (IMF) in longissimus muscle compared to bulls (5.59 vs. 2.07%). Greater concentration of monounsaturated fatty acids was observed in beef loins of steers (P<0.01), while bulls trend to shown higher (P = 0.08) polyunsaturated fatty acids and higher elongase activity (P<0.05). Thus, differences in gene expression were associated with differences in IMF deposition (marbling). Even after 180 days on feed, crossbred young bulls does not produce meat with adequate IMF and better fatty acid profile than steers.
Keywords: Carcass; Lipid metabolism; Marbling; Meat quality; Molecular biology